Particle size analysis of yellowfin tuna (Thunnus albacares) skin collagen powder using papain-soluble collagen method with varying NaCl concentrations: an experimental laboratory - Fatryana, Destya Arizha; Rahmitasari, Fitria; Nanik K., Chaterina Diyah; Rizal, Moh. Basroni; Winias, Saka (Padjadjaran Journal of Dentistry, 2024)
ABSTRACTIntroduction: The skin of yellowfin tuna (Thunnus albacares) contains high protein, which could potentially be a halal collagen product. Collagen extraction using the papain-soluble collagen method has the advantage of producing a higher collagen yield compared to the acid method. Particle size, one of the physical properties of collagen, plays a crucial role in its efficacy in dentistry. This study aims to analyze the particle size of collagen powder synthesized   from Thunnus albacares skin using the papain-soluble collagen method, with varying concentrations of NaCl. Methods: Type of research is an experimental laboratory. Thunnus albacares skin was synthesized by chopping, cleaning, and soaking in a 0.1 M NaOH solution. The extraction process used the enzyme papain and 0.5 M of acetic acid. Samples were divided into four groups, each with different concentrations of NaCL: 0, no NaCL;, 0.9 M NaCl, 1.3 M NaCl, and 1.7 M NaCl. After centrifugation, the samples were freeze-dried. The particle size of collagen powder was measured using a Particle Size Analyzer test tool. The data collected was then analyzed using the Mann-Whitney test. Results: Particle size distributions are as follows: K group (3.36 nm), P1 (1.842 nm), P2 (3.36 nm), and P3 (10.12 nm). There is a significant difference in groups K-P1 and P3, P1-P2 and P3, and P2-P3 (p<0.05). However, there is no significant difference in groups K-P2 (p>0.05). Conclusion: Particle size of this research produced nano-sized collagen powder, with the lowest particle size observed in the 0.9 M NaCl group, measuring at 1.842 nm. The particle size increased in the group without NaCl and in the 1.3 M NaCl group at 3.36 nm, and reached the highest value in the 1.7 M NaCl group at 10.12 nm.